New approaches to risk assessment of chemical mixtures. (3rd January 2019) - Hayes, A Wallace; Li, Roman; Hoeng, Julia; Iskandar, Anita; Peistch, Manuel C; Dourson, Michael L
Assessing the risk of chemical mixtures is an intricate process that should integrate published laboratory data; comparisons with the composition, toxicity, and functionality of similar mixtures; complete analytical characterization of the mixture components; and in silico modeling. Various tiered assessment protocols have been proposed to address this need, and these protocols may be adapted on a case-by-case basis for both mixture-based and component-based evaluations. Emerging technologies have enabled rapid mixture testing in alternative animal models, such as human organotypic cultures and zebrafish. In addition, quantitative modeling that uses systems toxicology approaches can identify exposure-induced cellular and molecular alterations that would not be detected by standard toxicology assays. This review summarizes the approaches to risk assessment of complex chemical mixtures as presented at the Eighth International Congress of the Asian Society of Toxicology, June 2018.